Intraosseous Regional Administration of Prophylactic Antibiotics in Total Knee Arthroplasty - Zoe Wells; Mark Zhu; Simon W. Young (Antibiotics, 2022)
Prosthetic joint infection (PJI) after total knee arthroplasty is a devastating complication. With the development of antibiotic resistance, a safe and effective means of delivering antibiotic prophylaxis is needed. Intraosseous regional antibiotics (IORA) achieve higher local concentrations of antibiotics with fewer systemic side effects. Previous studies have proven the safety of IORA, whereas animal models have proven it to be more effective than intravenous antibiotics for preventing infection following surgery. Recently, large-scale retrospective studies have also demonstrated lower PJI rates following TKA when IORA is used when compared to routine intravenous prophylaxis. In this article, we propose an evidence-based method for the administration of intraosseous antibiotics in TKA, cover the up-to-date data supporting its use, and explore future directions for additional research.